Transactions on edutainment VI - Pan, Zhigeng; Cheok, Adrian David; Müller, Wolfgang (Lecture Notes in Computer Science, 2011)
Summary.This journal subline serves as a forum for stimulating and disseminating innovative research ideas, theories, emerging technologies, empirical investigations, state-of-the-art methods, and tools in all different genres of edutainment, such as game-based learning and serious games, interactive storytelling, virtual learning environments, VR-based education, and related fields. It covers aspects from educational and game theories, human-computer interaction, computer graphics, artificial intelligence, and systems design. The 6th volume in this series represents a selection of 7 contributions from DMDCM 2011, the 5th International Conference on Digital Media and Digital Content Management, held in Chongqing, China, in December 2011, as well as 18 contributions from CASA 2011, the 24th International Conference on Computer Animation and Social Agents, held in Chengdu, China, in May 2011.